Towards flux-tunable superconducting coplanar waveguide resonators for inductive coupling to levitated superconducting particles - Mirkhan, Avan (My University, 2022)
Superconducting magnetic levitation is a promising technique to study potential limits of quantum mechanics for mesoscopic objects due to the levitated object being extremely isolated from the environment. Using optomechanics techniques, the centre-of-mass motion of a levitated particle can be controlled and cooled down to its motional ground-state thereby bringing it into the quantum regime. This would enable macroscopic quantum experiments as well as ultrasensitive force and acceleration sensing. In order to realize this, the motion of the particle’s centre-of-mass would be coupled to a flux-tunable superconducting resonator, which would allow control of the particle motion through the state of the resonator. This thesis investigates the microwave properties of superconducting coplanar waveguide (CPW) resonators. At first, non-flux tunable CPW resonators were fabricated from Aluminum and Niobium and measured in a cryostat at mK temperatures. The best performing CPW resonators achieved unloaded quality factors of ~10^5 and ~10^6 at 10^6 average number of intra-cavity photons for Aluminum and Niobium, respectively. The quality factors of these resonators were found to be one order of magnitude lower for Al, but higher for Nb, when compared to the state-of-the-art. Subsequently, flux-tunable resonators were fabricated by embedding a SQUID into Aluminum-based CPW resonators. The flux tunability of these resonators was studied and was found to be much lower than expected. The reason for the low tunability was due to the fabrication process of the Josephson junctions of the embedded SQUID, in which the junction width was too wide causing an excess amount of aluminum to have deposited onto the substrate. Based on these identified issues, suggestions have been proposed to improve upon the fabrication of flux-tunable CPW resonators, such that in the future the desired frequency tuning through a change in magnetic flux can be observed.
Keywords: superconductivity; magnetic levitation; superconducting circuit; quantum optics